Sustainable Rural Development and Wealth Creation: Five Observations Based on Emerging Energy Opportunities. (February 2014) - Pender, John L.; Weber, Jeremy G.; Brown, Jason P.
In this article, the authors argue that better data and research on rural wealth creation are greatly needed and present a conceptual framework to help guide such research. The authors then discuss five observations about rural wealth creation, based on examples drawn from the recent literature on emerging energy industries in rural America. The cases show that the types of data needed to draw conclusions about wealth effects of new development are highly contextual. The framework can help researchers think about the types of data needed to assess policy.